A role of air in complex elastic modulus measurements of solid samples by transmissibility methods - ZIÓŁKOWSKI, W.; ŚLIWIŃSKI, A. (Archives of Acoustics, 1993)
Anomalous dependence of visco-elastic parameters against frequency for solid polymers measured both in conditions of surrounding air as well as in vacuum were examined. In theoretical consideration the single system of one degree of freedom for representing a sample was assumed together with the presence of friction force introduced by the air. The values of E and η were measured in the air (105 Pa) and in the vacuum (102 Pa) conditions against frequency f from 20 – 2 x 10^3 Hz. The results show essential differences for both conditions. A comparison between numerical and experimental curves are presented. Anomalous behaviour of E(f) and η(f) against frequency in the air is essential for polymers of small values of Young modulus up to 106 N/m^2. The damping influence of the air having essential contribution in measurements of complex elastic modulus in light polymers must be taken into account when using the E, and η in situations the knowledge of exact values of those quantities is required, for example when mechanisms of internal friction in polymers are evaluated.